2012
DOI: 10.1080/0028825x.2012.662904
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype analysis in two species ofSolanum(Solanaceae) Sect.Cyphomandropsisbased on chromosome banding

Abstract: To contribute to the cytogenetic characterisation of the Cyphomandra clade of Solanum, fluorescence banding and silver staining were performed on Solanum fusiforme and Solanum stuckertii for the first time. Both species had 2n 024 chromosomes. Solanum fusiforme had a karyotype consisting of 9m ' 3sm chromosome pairs; one pair had active nucleolar organiser regions (NORs). Solanum stuckertii had 8m ' 4sm chromosome pairs with two pairs having active NORs. The two species exhibit similar amounts (11%) of constit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 34 publications
0
8
0
8
Order By: Relevance
“…The Cyphomandra clade is an exception with chromosome sizes ranging from 3 to 14 μm (e.g. Pringle and Murray 1991;Moscone 1992;Miguel et al 2012), as found here in S. crispum with chromosomes longer than 4 μm.…”
Section: Discussionmentioning
confidence: 91%
“…The Cyphomandra clade is an exception with chromosome sizes ranging from 3 to 14 μm (e.g. Pringle and Murray 1991;Moscone 1992;Miguel et al 2012), as found here in S. crispum with chromosomes longer than 4 μm.…”
Section: Discussionmentioning
confidence: 91%
“…In some cases, NORs appear to be terminal after silver staining, probably because microsatellites are no longer recognizable after applying this banding method because of their small size, a phenomenon that has been observed in Capsicum and Solanum (Moscone et al 1995, Miguel et al 2012.…”
Section: Nucleolar Activitymentioning
confidence: 99%
“…The studied species have comparatively low CMA+/DAPIÀ heterochromatin amount exhibited at the satellites (terminal) and some intercalary bands. Heterochromatin type GC-rich loci are coincident with 45S ones and therefore NOR-associated, as observed in most Solanaceae species studied so far Miguel et al 2012;Scaldaferro et al 2013;Chiarini et al 2014). It is known that in most plant species, ribosomal DNA is rather GC-rich (Roa & Guerra 2012).…”
Section: Karyotype Changes and Chromosomal Evolutionmentioning
confidence: 77%